Exosomes in oral squamous cell carcinoma: functions, challenges, and potential applications - Bo Zhao; Bo Zhao; Zuntai Li; Ronghua Li (Frontiers in Oncology)
Oral squamous cell carcinoma (OSCC) accounts for approximately 90% of all oral cancers, significantly impacting the survival and quality of life of patients. Exosomes, small extracellular vesicles released by cells, play a crucial role in intercellular communication in cancer. Nevertheless, their function and mechanism in OSCC remain elusive. Search Pubmed, Web of Science, and Cochrane Library using keywords OSCC, exome, diagnosis, and treatment to review the research progress of exome in OSCC. Based on these results, this review starting from the biosynthesis, structure, and contents of exosomes, elaborates on the research progress of exosomes in the diagnosis and treatment of OSCC. It explores the potential of exosomes in the diagnosis and treatment of OSCC, and briefly describes the challenges researchers currently face.